Muslim citizens in the West spaces and agents of inclusion and exclusion - Yasmin, Samina; Markovic, Nina (Routledge, 2016)
Drawing upon original case studies spanning North America, Europe and Australia, Muslim Citizens in the West explores how Muslims have been both the excluded and the excluders within the wider societies in which they live. The book extends debates on the inclusion and exclusion of Muslim minorities beyond ideas of marginalisation to show that, while there have undoubtedly been increased incidences of Islamophobia since September 2001, some Muslim groups have played their own part in separating themselves from the wider society. The cases examined show how these tendencies span geographical, ethnic and gender divides and can be encouraged by a combination of international and national developments prompting some groups to identify wider society as the 'other'. Muslim and non-Muslim scholars and practitioners in political science, social work, history and law also highlight positive outcomes in terms of Muslim activism with relationship to their respective countries and suggest ways in which increasing tensions felt, perceived or assumed can be eased and greater emphasis given to the role Muslims can play in shaping their place in the wider communities where they live.